2014
DOI: 10.7314/apjcp.2014.15.19.8447
|View full text |Cite
|
Sign up to set email alerts
|

Parameters for Predicting Granulosa Cell Tumor of the Ovary: A Single Center Retrospective Comparative Study

Abstract: Background: To evaluate factors for predicting the granulosa cell tumor of the ovary (GCTO) pre-operatively. Materials and Methods: This retrospective designed study was conducted on 34 women with GCTO as the study group and 76 women with benign ovarian cysts as the control group. Data were recorded from the hospital database and included age, body mass index (BMI), parity, serum estradiol (E 2 ) levels, diameter of the mass, ultrasonographic features, serum CA125 level, risk of malignancy index (RMI), duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Ovarian adult granulosa cell tumor, accounting for 95% of ovarian granulosa cell tumor, mainly occurs in perimenopausal and postmenopausal women and exhibits unpredictably late recurrence features [3][4][5][6]. Among the multiple prognostic factors reported, menopause, tumor diameter, estrogen and CA125 levels, International Federation of Gynecology and Obstetrics (FIGO) staging, residual lesions, multisite recurrence, and presence of mitotic figures have been mentioned as factors associated with the prognosis [7][8][9][10]. The treatment and outcomes of recurrent AGCOT remain uncertain, as there have only been a small number of case reports [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian adult granulosa cell tumor, accounting for 95% of ovarian granulosa cell tumor, mainly occurs in perimenopausal and postmenopausal women and exhibits unpredictably late recurrence features [3][4][5][6]. Among the multiple prognostic factors reported, menopause, tumor diameter, estrogen and CA125 levels, International Federation of Gynecology and Obstetrics (FIGO) staging, residual lesions, multisite recurrence, and presence of mitotic figures have been mentioned as factors associated with the prognosis [7][8][9][10]. The treatment and outcomes of recurrent AGCOT remain uncertain, as there have only been a small number of case reports [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that elevated platelet count is associated with adverse outcomes in different malignancies. Moreover, it was claimed that the PLR and NLR could be used as a diagnostic marker for certain gynecologic cancers (Yesilyurt et al, 2014;Yildirim et al, 2014). Raungkaewmanee et al (2012) designed a retrospective study to determine whether preoperative PLR associated with diagnosis and prognosis of epithelial ovarian cancer.…”
Section: Figure 1 Roc Curve Analysis For Plr In Prediction Of Adolesmentioning
confidence: 99%
“…There are several markers such as Ca-125 and vascular endothelial growth factor (VEGF), that have been studied in the preoperative period for the early diagnosis of ovarian cancer (15) . Yeşilyurt et al evaluated Ca-125 as a marker for GCTO and showed increased mean values in GCTO (64.5±130.3 IU/mL) (11) .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, NLR was found to be statistically significantly different in GCTO and benign ovarian masses. ROC curve analysis has shown that NLR could be a differentiating factor in the preoperative prediction of GCTO (11) . In a more recent meta-analysis, a significant relationship was determined between high NLR and poor general survival (HR: 1.88, 95% CI 1.30-.73) and shorter progression-free survival (HR 1.65, 95% CI 1.18-2.29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation